Converging evidence from fMRI and aphasia that the left temporoparietal cortex has an essential role in representing abstract semantic knowledge. (August 2015) - Skipper-Kallal, Laura M.; Mirman, Dan; Olson, Ingrid R.
Abstract: While the neural underpinnings of concrete semantic knowledge have been studied extensively, abstract conceptual knowledge remains enigmatic. We present two experiments that provide converging evidence for the involvement of key regions in the temporoparietal cortex (TPC) in abstract semantic representations. First, we carried out a neuroimaging study in which participants thought deeply about abstract and concrete words. A functional connectivity analysis revealed a cortical network, including portions of the TPC, that showed coordinated activity specific to abstract word processing. In a second experiment, we tested participants with lesions involving the left TPC on a spoken-to-written word matching task using abstract and concrete target words presented in arrays of related or unrelated distractors. The results revealed an interaction between concreteness and relatedness: participants with TPC lesions were significantly less accurate for abstract words presented in related arrays than in unrelated arrays, but exhibited no effect of relatedness for concrete words. These results confirm that the TPC plays an important role in abstract concept representation and that it is part of a larger network of functionally cooperative regions needed for abstract word processing.